Explanation Materials for Landscape Reserve “Zelena Valley” Creation (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The authors review the arguments for creation of nation-wide value landscape reserve Zelena Valley (Kryvyi Rih Region). We characterized rare vegetation and flora and proposed original criteria for that. It allowed us to estimate the sozological value of Zelena Valley landscape system.
Keywords: Kryvyi Rih Region, ecological network, Zelena Valley, vegetation cover, rare flora, landscape system.